University choice: The role of expected earnings, non-pecuniary outcomes, and financial constraints - Adeline Delavande; Basit Zafar (Federal Reserve Bank of New York, 2014)
We investigate the determinants of students' university choice, with a focus on expected monetary returns, non-pecuniary factors enjoyed at school, and financial constraints, in the Pakistani context. To mitigate the identification problem concerning the separation of preferences, expectations, and markets constraints, we combine rich data on individual-specific subjective expectations about labor market and non-pecuniary outcomes, with direct measures of financial constraints and students' stated school choice both with and without financial constraints. Estimates from a life-cycle model show that future earnings play a small (but statistically significant) role. However, non-pecuniary features, such as a school's ideology, are major determinants. Data on students' choices without financial constra ints allow for the out-of-sample validation of the model, which shows a strikingly good fit. Our results demonstrate that 37 percent of students are financially constrained in their choice of university, and that implementing policies relaxing financial constraints would increase students' average lifetime subjective expected utility by 21 percent. From a methodological stand point, we find that ignoring non-pecuniary factors, uncertainty related to employment and drop-out, or direct measures of financial constraints yields biased estimates - a result that underscores the importance of having data on these elements for understanding university choice in any context.
Keywords: D81; D84; I21; I23; 330; school choice; credit constraints; subjective expectations